O significado do uso dos medicamentos Psicotrópicos na vida cotidiana: Uma revisão sistemática - Agnes Fonseca Ribeiro Filardi (2015)
Introduction: The use of psychotropic drugs to treat problems of everyday life is a growing phenomenon in many countries. Objective: To understand the use of psychotropic medications from the perspectives of health care professionals and patients. Method: A systematic review of qualitative studies that addressed the use of psychotropic medication by adults to deal with stress or negative events in their personal lives. This systematic review was conducted in the databases Central (Cochrane), Psycoinfo and Lilacs, including gray literature and manual search (june / 2015). Results: We identified 581 publications that were evaluated in stages and 26 met the inclusion criteria with a total of 876 participants including physicians, health professionals and patients. Health professionals were concerned about the dependence of patients on medications and the pressure to prescribe psychotropic drugs. The doctors felt touched by patients problems and showed empathy by prescribing. Patients felt unable to solve their problems and sought medications as a solution. Conclusion: The use of psychotropic drugs could be connected to medical and patient characteristics, or their interaction, associated with social problems.